Closing the loop on take, make, waste: Investigating circular economy practices in the Swedish fashion industry. (15th April 2021) - Brydges, Taylor
Abstract: The fashion industry is one of the most wasteful consumer industries in the world. Through the advent of fast fashion – trendy, low-cost clothing produced by global fashion brands – clothing has evolved from a durable good to a daily purchase. In recent years, the concept of the circular economy, a framework for a more efficient, closed-loop economy, has emerged as a key way forward in the transition to a more sustainable and less wasteful fashion industry. This paper investigates how the Swedish fashion industry has implemented circular economy principles. Drawing on interviews with the founders, CEOs, and/or brand sustainability managers of 19 Swedish fashion brands, this article maps circular economy strategies across key stages: take, make, and waste. Crucially, for the fashion industry to move towards circularity, this paper argues that brands must integrate these strategies across supply chains, rather than limiting them to the waste stage. The analysis explores the gaps between circular economy principles and practice, identifying challenges inherent in fashion brand approaches. It concludes with recommendations for further study of the circular economy and the fashion industry.